Probiotics for Preterm Infants: A Strain-Specific Systematic Review and Network Meta-analysis. Issue 1 (July 2018) - van den Akker, Chris H.P.; van Goudoever, Johannes B.; Szajewska, Hania; Embleton, Nicholas D.; Hojsak, Iva; Reid, Daan; Shamir, Raanan
ABSTRACT: Objectives: Several randomized controlled trials (RCTs) on the use of probiotics to reduce morbidity and mortality in preterm infants have provided inconsistent results. Although meta-analyses that group all of the used strains together are suggesting efficacy, it is not possible to determine the most effective strain that is more relevant to the clinician. We therefore used a network meta-analysis (NMA) approach to identify strains with greatest efficacy. Methods: A PubMed search identified placebo-controlled or head-to-head RCTs investigating probiotics in preterm infants. From trials that recorded mortality, necrotizing enterocolitis, late-onset sepsis, or time until full enteral feeding as outcomes, data were extracted and Bayesian hierarchical random-effects models were run to construct a NMA. Results: Fifty-one RCTs involving 11, 231 preterm infants were included. Most strains or combinations of strains were only studied in one or a few RCTs. Only 3 of 25 studied probiotic treatment combinations showed significant reduction in mortality rates. Seven treatments reduced necrotizing enterocolitis incidence, 2 reduced late-onset sepsis, and 3 reduced time until full enteral feeding. There was no clear overlap of strains, which were effective on multiple outcome domains. Conclusions: This NMA showed efficacy in reducing mortality and morbidity only in a minority of the studied strains or combinations. This may be due to an inadequate number, or size, of RCTs, or due to a true lack of effect for certain species. Further large and adequately powered RCTs using strains with the greatest apparent efficacy will be needed to more precisely define optimal treatment strategies. Abstract : Supplemental Digital Content is available in the text